Dampak Psikososial Akibat Bencana Lumpur Lapindo - Mundakir Mundakir (Jurnal Ners, 2011)
Introduction: Lapindo mud disaster that occurred since 29 May 2006 is considered as the longest disaster that occurred in Indonesia. This disaster has caused damage and lost of property which has been affecting the viability of the residents of the affected areas. Psychosocial well being is one af the impacts of disaster. Research was conducted using qualitative design with descriptive phenomenology method. The purpose required of this research was to identify the psychological impact, social impact, and hope for the settlement of problems and health services.Method: Number of participants were involved in this research based on the saturation of data was 7 people. This study used purposive sampling technique using the key informant. Procedure of data collection techniques using depth interviews with a semi-structured form of used questions. The Digital Voice Record was utilized to record the interviews, and verbatim transcripts made and analyzed using the methods of Colaizi (1978, in Daymon and Dolloway, 2008).Result: This study revealed 9 theme of core and 2 additional theme. Nine the core theme is emotional changes, cognitive changes, coping mechanism, changes in family function, changes in social relationships, social support, hope to the problem to the government and PT Lapindo, physical health service needs and psychological health.Conclusion: While two additional theme that is risk and growth trouble, and distres spiritual. Conclusion of this research society of victim of mud of Lapindo experience of impact of psikosoial and hope to government and PT Lapindo settle the payment phase II (80%) and also provide service of health of physical and also psikososial. This research recommend the importance of intervention of psikososial to society of victim and research of continuation after society of victim take possession of new residences.